Oral health status and related factors of Aetas Living in Nabuklod Resettlement area, Floridablanca, Pampanga - Maghirang, Rudgie Marie
In the country, oral diseases remain one of the most prevalent diseases. Indigenous groups are one of the most neglected sectors in the country owing to the fact that these people prefer to live in isolated and far-off places making health programs and services inaccessible to them. This study aims to determine the oral health status and related factors of Aetas living in Nabuklod Resettlement Area, Floridablanca, Pampanga. The researchers made use of interviews and actual dental examination in order to determine and describe the DMFT, OHI-S, dental beliefs, oral hygiene practices and the diet of the population. Based on findings of the study, it was observed that the population generally has poor oral health conditions brought primarily by the fact that oral hygiene is given less priority, if not neglected. Financial constraints and lack of motivation are major factors for this observation.